Expanding scope: the role of legitimacy and legitimation in the adoption of consumption-based carbon accounting in European cities - Hasan, Lisa N.; Deshayes, Eloise; Brown, Will (Frontiers in Sustainable Cities, 2025)
IntroductionIn the pursuit of carbon neutrality, cities are increasingly measuring their greenhouse gas emissions. Most cities focus on territorial emissions tied to production, excluding consumption-driven emissions outside city boundaries. This gap is critical, as Scope 3 emissions can represent as much as 80% of cities’ carbon footprint. Addressing this limitation calls for urban consumption-based carbon accounting (CBCA). Yet, despite CBCA’s relevance for climate action, it has struggled to gain political legitimacy within European cities. This raises the question: How can urban CBCA achieve political legitimacy?MethodsBased on semi-structured expert interviews with municipal practitioners in 17 European cities, we explore the barriers, enablers, and strategies used to enhance CBCA legitimacy. We develop a framework that describes the process of CBCA legitimation from exploration to political legitimacy.ResultsResults show that urban CBCA’s legitimacy rests primarily on cognitive legitimacy. Throughout the legitimation process, data plays a crucial role. Initially, access to data and clear calculation methodologies contributes to comprehensibility by making urban CBCA seem plausible and predictable. However, once CBCA comprehensibility is achieved metrics become less important than acting in ways that align with the broader understanding of consumption-based emissions. Finally, as CBCA measures affect citizens more directly, metrics resurface as means to validate impacts of past policy decisions and thus reinforce CBCA’s legitimacy.DiscussionWe discuss the various pitfalls and promising strategies to build political legitimacy for urban CBCA. This research contributes to the understanding of how urban CBCA legitimacy evolves over time. The legitimation framework developed can help inform policymakers in their endeavors to advance CBCA legitimation and institutionalization.